TIPOLOGI SUMBER PENAFSIRAN IBNU ABBAS DALAM TAFSá¿™R AL-á¹¬ABARÄª - Herfinawati Nasution (AL ITQAN: Jurnal Studi Al-Qur'an, 2018)
Ibn Abbas got the nickname Tarjaman Al-Qur ʻan from the scholars. This indicates his expertise and depth in understanding al-Qur ʻan. His coronation as the foundation of the science of interpretation indicates the depth of experience one has in the world of interpretation. The interpretive construction in the form of history makes it difficult for the reader to describe the pattern of interpretation carried out. However, searching and studying the narrations can describes patterns of interpretation, themes, pathways, and patterns of interpretation. Therefore, this study focuses on the history of Ibn Abbas's interpretation of QS. al-Baqarah: 1-141. The results of this study indicate that the themes of Ibn Abbas' narrative are divided into seven types, ghaibiyat originating from the Prophet, characteristics derived from ijitihad, the meaning of the recitation of verses coming from Arabic, stories sourced from the Prophet and friends, Allah's promises are from the Prophet, the name and asbāb al-nuzūl is also a conviction that comes from the Prophet.